Implementasi Cloud Storage Sebagai Data Center di SMK IGASAR Pindad - Ali Akbar Rismayadi; Dwiki Yuliawa (Jurnal Computech & Bisnis (e-Journal), 2017)
Computer network in SMK IGASAR PINDAD is still stand alone and often experience problems in data storage which includes data sharing using only flash and external hard drive. Unavailability of data backup automatically and data storage not yet central, hence required an alternative technology that can be implemented at SMK IGASAR PINDAD, construction of cloud storage system as data center. The method used is network design and cloud server configuration. As a Service (IAAS) infrastructure as a service and security model uses Secure Socket Layer (SSL) Let's encrypt so that cloud storage enables users to access, sync, share data and centralized data storage.Keywords: IAAS, data center, SSL.